Terminologia da mandioca na comunidade quilombola Oxóssi da Ribeira - GONÇALVES, Cleide Loureiro (2019)
The present work, titled Terminology of cassava in the Quilombola Community Oxóssi da Ribeira is a terminological study, whose object is the elaboration of an illustrative terminology glossary, which aims to show the knowledge of specialty domain in an organized, to describe and define the possible terms of the language used for the communication of the farmers who work in cassava cultivation, this being the largest source of income of the Municipality, since it is one of the main agricultural product that contributes most to the subsistence and income generation of the community . In view of this, we selected terms that were divided into semantic fields related to cassava, cassava cultivation, processing, and cassava derivatives and instruments, terms that were raised during the research. The proposal used to create the corpus emphasizes the study of languages of specialties that contributes to the phenomenon of terminological linguistic variations based on the theoretical methodological guidelines of the Lexical Sciences, such as BARROS (2004), FAULSTICH (1995), KRIEGER and FINATTO (2004). As well as, identification of the nature and delimitation of the corpus; field research with terminological data collection, as well as interview techniques with oral narratives of the informants, through audio recordings accompanied by the use of realia and Semantic-Lexical Questionnaire (QSL) that was applied to the 5 informants and digital photo captures for Finally, an illustrated terminology glossary constituting 109 entries was drawn up.